Sex-gender and atrial fibrillation treatment in the AntiThrombotic Agents in Atrial Fibrillation (ATA-AF) study - Cecilia Politi; Tiziana Ciarambino; Letizia Riva; Stefania Frasson; Donata Lucci; Gualberto Gussoni; Lucio Gonzini; Mauro Campanini; Michele Gulizia; Giuseppe Di Pasquale; Giovanni Mathieu; on behalf of ATA-AF Steering Committee and Investigators (Italian Journal of Medicine, 2016)
Atrial fibrillation (AF) is the most common cardiac arrhythmia. This analysis aimed to determine the sex-gender differences in patients with AF enrolled in the observational AntiThrombotic Agents in Atrial Fibrillation (ATA-AF) study. The study was conducted in 360 centers in Italy. During a 4-week period, all consecutive inpatients and outpatients aged ≥18 years, with a documented primary or secondary diagnosis of AF, were included. A total of 7148 patients (47% females) were enrolled. Females were significantly older, they more frequently needed assistance and were affected by severe cognitive impairment. The preferred anti-arrhythmic strategy in both genders was heart rate control (females: 54.7%, males: 48.4%, P<0.0001). Among non-valvular AF patients (n=4845, females=2139), females displayed greater prevalence of CHA2DS2-VASc ≥2 (96.1% vs 80.7%; P<0.0001) and CHADS2 ≥2 (68.2% vs 60.4%; P<0.0001). More females were at high risk of bleeding (31.3% vs 26.1%; P<0.0001). Oral anticoagulants (OAC) were used in 55.5% of non-valvular AF patients, less frequently in females (50.9% vs 59.2%; P<0.0001). High hemorrhagic risk [odds ratio (OR) 5.94, 95% confidence interval (CI) 4.70-7.51], paroxysmal AF (OR 3.88, 95% CI 3.11-4.83), cognitive (OR 2.18, 95% CI 1.57-3.02) and functional impairment (OR 1.31, 95% CI 1.02-1.67) were significantly related with non-prescription of OAC, while age 75 was not (1.00, 95% CI 0.79-1.26). This study defines sex-gender differences in AF patients, including lower OAC prescription in females despite of higher thrombotic risk. Concomitant higher hemorrhagic risk and other characteristics that were more frequent in females (i.e., severe cognitive and functional impairment) may at least partly explain this trend towards gender-related under-prescription of OAC.